Bending capacity of lattice joist of steel fiber reinforced precast concrete slab - Ahmed N. M. Almassri, 1990-, author 610580 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Kejuruteraan (Awam - Struktur))